Octagonal Shaped Metamaterial Absorber Based Energy Harvester - Fatih Ozkan ALKURT; Olcay ALTINTAS; Mehmet BAKIR; Ahmet TAMER; Faruk KARADAG; Mehmet BAGMANCI; Muharrem KARAASLAN; Emin UNAL; Oguzhan AKGOL (Medžiagotyra, 2018)
In this study, a novel octagonal shaped metamaterial based broadband absorber is proposed for energy harvesting at WIMAX wireless communication band. The proposal has an absorption of 99.97 % at 5.5 GHz with a bandwidth of 1 GHz between 5 GHz and 6 GHz in Transverse Electric (TE) mode. Transverse Electric (TE), Transverse Magnetic (TM) and Transverse Electromagnetic (TEM) modes are studied numerically in this paper. In TM and TEM modes, proposed structure has absorption of nearly 96 % and 98 % respectively at 6 GHz. The proposed structure is polarization angle independent which is important for energy harvesting applications. Energy harvesting application is realized by using resistive loads on the design, simulations are parametrically studied on resistive loads and experimental study is realized for reflection coefficient measurement and compared with simulated results. Both experimental and simulated results are complying with each other. The proposed structure has different usage areas in stealth areas, detection and imaging. DOI: http://dx.doi.org/10.5755/j01.ms.24.3.18625